Association Between Sarcopenia and Depressive Symptoms in Chinese Older Adults: Evidence From the China Health and Retirement Longitudinal Study - Gao, Ke; Ma, Wen-Zhuo; Huck, Scarlett; Li, Bo-Lin; Zhang, Li; Zhu, Jiao; Li, Tian; Zhou, Dan (Frontiers in Medicine, 2021)
Background: Little is known about whether sarcopenia predicts incident depressive symptoms in older adults. Using the nationally representative data from the China Health and Retirement Longitudinal Study (CHARLS), we conducted cross-sectional and longitudinal analyses to estimate the association between sarcopenia and depressive symptoms among older adults. Methods: The sample comprised 7706 participants aged at least 60 years (50.6% women; mean age 68.0 ± 6.5) from the CHARLS 2015. Based on the Asian Working Group for Sarcopenia 2019 (AWGS 2019) criteria, sarcopenia status was classified into 3 types: no-sarcopenia, possible sarcopenia and sarcopenia. Depressive symptoms were assessed using the validated 10-items of Center for Epidemiologic Studies Depression Scale. Cross-sectional analysis was used to examine the relation between sarcopenia status and depressive symptoms. A total of 4652 participants without depressive symptoms were recruited from the same cohort in 2015 and were followed up in 2018. Cox proportional hazards regression models were conducted to examine the effect of sarcopenia status on subsequent depressive symptoms with the report of hazards ratio (HR). Results: The prevalence of depressive symptoms in total populations, no-sarcopenia, possible sarcopenia and sarcopenia individuals were 27.1% (2085/7706), 21.5% (927/4310), 33.6% (882/2627), 35.9% (276/769), respectively. Both possible sarcopenia (OR: 1.75, 95% CI: 1.46–2.10) and sarcopenia (OR: 1.64, 95% CI: 1.23–2.19) were positively associated with higher odds of depressive symptoms (all P < 0.01). During the 3.7 years of follow-up, 956 cases (20.6%) with incident depressive symptoms were identified. In the longitudinal analysis, individuals with the diagnosed possible sarcopenia (HR:1.27, 95% CI: 1.01–1.58) and sarcopenia participants (HR:1.49, 95% CI: 1.06–2.09) were more likely to have new onset depressive symptoms than no-sarcopenia peers. Conclusions: Both possible sarcopenia and sarcopenia, assessed using the AWGS 2019 criteria, were independent predictors for the occurrence of depressive symptoms among Chinese older adults. Our findings provided the new evidence supporting the longitudinal connection between sarcopenia and mental health problems, it also provides further justification for timely identification and management of both possible sarcopenia and sarcopenia as part of comprehensive strategies to fight against depressive symptoms.